Prescribing Cascade Complicating a Geriatric Patient - Shambo Samrat Samajdar; Shatavisa Mukherjee; Sougata Sarkar; Nandini Chatterjee; Mrinal K Roy; Jyotirmoy Pal; Santanu K Tripathi; Shashank R Joshi (Journal of the Indian Academy of Geriatrics, 2024)
Prescribing cascades entail misinterpreting drug-related adverse events as new medical problems, resulting in unnecessary prescriptions and potential harm, especially in the elderly, leading to adverse outcomes like falls, cognitive defects, and increased health-care costs. For geriatric patients with complex medical histories, the intricacies of symptom differentiation and polypharmacy poses further challenges. This report focuses on managing a geriatric patient with multiple conditions, highlighting the risks and complexities of prescribing cascades.